Clinical profile of the functionally selective glucocorticoid receptor agonist BI 653048 in healthy male subjects. (4th May 2019) - Harcken, Christian; Scholl, Paul; Nabozny, Gerald; Thomson, David; Bianchi, Daniel
ABSTRACT: Background : An efficacious anti-inflammatory corticosteroid with reduced side effects has been long sought. We report the pooled results from three clinical proof-of-mechanism Phase I studies of BI 653048 in healthy subjects, a functionally selective, nonsteroidal glucocorticoid (GC). Research design and methods : Three Phase I trials were conducted: a single rising-dose study and a multiple rising-dose study to evaluate the safety, tolerability, and pharmacokinetics of BI 653048, and a multiple parallel-arm-dose study with intravenous lipopolysaccharide challenge to assess in vivo pharmacodynamics. The pharmacodynamics, efficacy, and safety of BI 653048 and prednisolone were compared. Results : Treatment with 200 mg BI 653048 was associated with a reduced expression of IL1R2, ITGB3, and SDPR versus 20 mg prednisolone; comparable levels of FKBP5, ZBTB16, and DDIT4 expression were observed. Changes in C-peptide, glucose, insulin, and cortisol were moderate compared with prednisolone. A greater reduction of osteocalcin was observed with 200 mg BI 653048 versus 20 mg prednisolone. Comparable anti-inflammatory efficacy was demonstrated for 200 mg BI 653048 and 20 mg prednisolone. BI 653048 was well tolerated in healthy subjects. Conclusion : BI 653048 demonstrated the desired anti-inflammatory effects of the nonsteroidal GC; however, the undesirable side-effect profile associated with GC steroids could not be disassociated from BI 653048. Trial registration: ClinicalTrials.gov identifier: NCT02217644. Trial registration: ClinicalTrials.gov identifier: NCT02217631. Trial registration: ClinicalTrials.gov identifier: NCT02224105.